2013
DOI: 10.21273/jashs.138.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression of Skinning Injury-responsive Genes in Sweetpotato

Abstract: Skinning injury in sweetpotatoes (Ipomoea batatas) is responsible for significant postharvest loss resulting from storage diseases and weight loss. Unfortunately, there is no report on the genes involved in wound healing of sweetpotato and a better understanding will facilitate improved breeding strategies. An annealing control primer (ACP) system was used to identify genes expressed after skinning injury of sweetpotato cultivar LA 07-146 storage roots. Using 20 ACPs, 63 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…DEG 5954.7 (CYP81A6), shown to confer resistance to bentazon in transgenic Arabidopsis, was constitutively elevated in MHR4 plants and its differential regulation co‐segregated with flucarbazone resistance in F 3 families. DIGE analysis showed that MHR4 plants contained higher levels of spot 25 ( O. sativa 76C4 P450), a wound‐inducible P450 (Table ). In contrast, DEG 6502 (CYP94C1), involved in jasmonate response and salt stress alleviation, was constitutively lower in MHR4 than HS1 plants.…”
Section: Discussionmentioning
confidence: 99%
“…DEG 5954.7 (CYP81A6), shown to confer resistance to bentazon in transgenic Arabidopsis, was constitutively elevated in MHR4 plants and its differential regulation co‐segregated with flucarbazone resistance in F 3 families. DIGE analysis showed that MHR4 plants contained higher levels of spot 25 ( O. sativa 76C4 P450), a wound‐inducible P450 (Table ). In contrast, DEG 6502 (CYP94C1), involved in jasmonate response and salt stress alleviation, was constitutively lower in MHR4 than HS1 plants.…”
Section: Discussionmentioning
confidence: 99%
“…RNA quality and quantity were determined using a spectrophotometer (NanoDrop ND-1000; Thermo Scientific, Wilmington, DE). cDNA synthesis and quantitative reverse transcription (qRT)-PCR were performed as described earlier (Effendy et al, 2013). Briefly, 2 mg of total RNA was reverse transcribed using an iScript cDNA synthesis kit (Bio-Rad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…A melting curve analysis was performed to ensure correct gene amplification product. The sweetpotato elongation factor 1-alpha [IbEF1a (Effendy et al, 2013)] (Table 1) was used as the reference gene for normalization of gene expression. Each qRT-PCR reaction was run in triplicate and each gene was tested twice using cDNA made from two independent RNA sample sets from total roots (drought and control).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of its origin, the sweetpotato genome is hexaploid and highly heterozygous, and this genetic complexity has slowed genome sequencing, assembly, and annotation over the past 10 years. Nevertheless, the available molecular resources for sweetpotato are rapidly expanding and include de novo assembled transcriptomes of sweetpotato and several of its predicted wild-type relatives ( Schafleitner et al, 2010 ; Wang et al, 2010 ; Tao et al, 2012 ; Xie et al, 2012 ; Effendy et al, 2013 ; Firon et al, 2013 ; Solis et al, 2014 , 2016 ; Ponniah et al, 2017 ), microsatellite, specific length amplified fragment (SLAF) and amplified fragment length polymorphism (AFLP) markers to characterize genetic diversity ( Bruckner, 2004 ; Techen et al, 2009 ; Schafleitner et al, 2010 ; Roullier et al, 2011 , 2013a , b ; Su et al, 2017 ), recently released draft genome assemblies ( Yang et al, 2016 ; Zhou et al, 2017 ) and whole chloroplast genomes of sweetpotato and wild relatives ( Munoz-Rodriguez et al, 2018 ). Diploid reference genome assemblies based on progenitor wild relatives, I. trifida and I. triloba , are now available for hexaploid I. batatas .…”
Section: Introductionmentioning
confidence: 99%